INFLUENCE OF HIGH-TEMPERATURE LOADING CONDITIONS ON CHANGES IN THE PHYSICAL STATE OF YTTRIUM-CONTAINING COATINGS - Kubich, Vadim; Fasol, Yelyzaveta; Cherneta, Oleg (Problems of Friction and Wear, 2024)
yttrium content varies linearly and significantly differs from the nature of the mass gain under the conditions of modelling dynamic loading in a burning iso-octane-propane-butane gas mixture at a temperature of 950-1020 ℃. It is determined that the maximum mass increase for gas-flame coatings under static loading is 30-35% at the yttrium concentration of 0.3-0.5%. However, for ionoplasma coatings with the same yttrium concentration, the mass gain is almost 2 times less than that of gas flame coatings. Comparing the peculiarities of changes in the rate of increase in the mass of coatings under dynamic conditions of high-temperature loading, a graphical model of changes in the physical state of coatings was obtained, according to which the minimum amount of secondary compounds will occur at the gas-flame method of formation with a yttrium concentration of 0.1% to 0.47%, at the ion-plasma method of formation with a concentration of 0.25% to 0.35% (under conditions of a slight increase in oxygen in the interaction medium). It was determined that, without taking into account the time of structural-phase transformations and chemical reactions, the weight gain of coating materials under static loading is much greater than under dynamic loading.